Retroperitoneal ganglioneuroma simulating lymphoma: An unusual case presentation - Charles K. Crawford, BS; Mohammad Yasrab, MD; Linda C. Chu, MD; Elliot K. Fishman, MD (Radiology Case Reports)
Ganglioneuromas of the retroperitoneum are rare cases of benign retroperitoneal tumors that arise from autonomic nerve fibers. Typically remaining asymptomatic even after growing very large, retroperitoneal ganglioneuromas are often discovered incidentally. Given the rather nonspecific, well-defined, smooth, or lobulated characteristics similar to most neurogenic tumors, retroperitoneal ganglioneuromas are sometimes difficult to diagnose. Surgical resection is the preferred treatment option intended to limit the chance of recurrence or malignant transformation; however, surgery can be restricted by local extension, such as encasement of blood vessels. In this article, we report the case of a 49-year-old female diagnosed with a retroperitoneal ganglioneuroma presenting as abdominal pain and fullness. We focus on the use of radiological imaging modalities to coordinate with surgical pathology for an optimized diagnosis and treatment plan.